Experimental Investigation of Carbon Dioxide Adsorbing Concrete Blocks Incorporating Zeolite and Dunite as Sustainable Mineral Admixtures (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The construction sector is facing growing challenges to reduce greenhouse gas emissions by adopting environmentally sustainable construction materials with lower carbon footprints. Among the emerging solutions, carbon dioxide (CO₂)-adsorbing concrete has attracted considerable attention because of its ability to capture atmospheric CO₂ while maintaining the engineering properties required for structural applications. This study experimentally evaluates the potential of developing sustainable concrete blocks with enhanced CO₂ adsorption capacity through the partial replacement of conventional materials with natural zeolite and Dunite. Concrete mixes containing different replacement proportions were prepared and assessed for both fresh and hardened properties. Workability, compressive strength, water absorption, and density were determined in accordance with the relevant Indian Standard specifications. In addition, the CO₂ adsorption capacity of the concrete blocks was evaluated to examine the effect of these mineral additives on carbon sequestration performance. The findings reveal that incorporating zeolite and Dunite improves the CO₂ adsorption capability of concrete while preserving satisfactory mechanical properties when used within optimal replacement limits. However, higher replacement levels reduce workability and compressive strength, primarily due to increased pore volume and weaker cementitious bonding within the concrete matrix. Overall, the results indicate that a balanced combination of zeolite and Dunite can produce sustainable concrete blocks with enhanced carbon capture potential and acceptable structural performance. The outcomes of this research provide valuable insights into the development of eco-friendly construction materials that can contribute to carbon mitigation efforts while supporting the long-term sustainability of the built environment.